Figurative Language as Social Criticism in Meet Nite Live's Economic Discourse - Ervina Damayanti; Avinta Ika Nurrahma (Global Expert: Jurnal Bahasa dan Sastra, 2026)
The development of digital communication technology has transformed the way media outlets deliver news, including economic news, which is increasingly presented in communicative ways through the use of figurative language. This study aims to describe the forms of figurative language and explain their functions as social criticism in the economic discourse of the Meet Nite Live program on Metro TV. The Study used a descriptive qualitative approach with a stylistic perspective. The data source of this study consists of the presenter’s utterances in the Meet Nite Live program broadcast on Metro TV’s YouTube channel throughout 2025. The researcher first identified episodes discussing economic topics, after which several of those episodes were randomly selected as the data source for the study. Data were collected using observation and note-taking techniques and analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The findings reveal that figurative language functions not only as an aesthetic element but also as a communication strategy to simplify economic issues while conveying social criticism. Three main categories of figurative language were identified: comparison, opposition, and emphasis. The comparison category includes personification, simile, metaphor, and allusion; the opposition category includes irony, cynicism, paradox, and antithesis; while the emphasis category includes repetition and hyperbole. The analysis demonstrates that each category serves a different function in constructing social criticism. Comparative figurative language concretizes abstract economic concepts; oppositional figurative language highlights the gap between expectations and socio-economic realities. In contrast, emphatic figurative language strengthens critical messages regarding issues such as unemployment, layoffs, taxation, rising living costs, and economic inequality. These findings indicate that stylistic analysis and social criticism analysis complement each other in explaining how lexical choices, shifts in meaning, and figurative expressions construct meaning and influence public understanding of economic realities. Keywords: Figurative language, social criticism, media discourse, stylistics, Meet Nite Live